Taking snapshots of the Web with a TEI camera. - Walker, D. (Computers & the Humanities, 1999)
Focuses on a project that aims to observe and capture language usage on the Web. Goal of the `Snapshot' project; Creation of an open corpus of World Wide Web documents; Re-encoding of the documents using the Text Encoding Initiative guidelines; Logical divisions in the markup found in HTML.